Sex‐specific effects of relaxin‐3 on food intake and body weight gain. (13th July 2016) - Calvez, Juliane; de Ávila, Camila; Timofeeva, Elena
Abstract : Relaxin‐3 (RLN3) is a neuropeptide that is strongly expressed in the pontine nucleus incertus (NI) and binds with high affinity to its cognate receptor RXFP3. Central administration of RLN3 in rats increases food intake and adiposity. In humans, RLN3 polymorphism has been associated with obesity and hypercholesterolaemia. Emerging evidence suggests that the effects of RLN3 may have sex‐specific aspects. Thus, the RLN3 knockout female but not male mice are hypoactive. RLN3 produced stronger orexigenic and obesogenic effects in female rats compared with male rats. In addition, female rats demonstrated higher sensitivity to lower doses of RLN3. Repeated cycles of food restriction and stress were accompanied by an increase in RLN3 expression and hyperphagia in female but not in male rats. Furthermore, stress‐induced binge eating in female rats was blocked by an RXFP3 receptor antagonist. RLN3 increased the expression of corticotropin releasing factor in the paraventricular hypothalamic nucleus in male but not in female rats. Conversely, in female rats, RLN3 increased the expression of orexin in the lateral hypothalamus. There is evidence that orexin directly activates the RLN3 neurons in the NI. The positive reinforcement of the RLN3 effects by orexin may intensify behavioural activation and feeding in females. Sex‐specific effects of RLN3 may also depend on differential expression of RXFP3 receptors in the brain. Given the higher sensitivity of females to the orexigenic effects of RLN3 and the stress‐induced activation of RLN3, the overall data suggest a possible role for RLN3 in eating disorders that show a higher propensity in women. Linked Articles: This article is part of a themed section on Recent Progress in the Understanding of Relaxin Family Peptides and their Receptors. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v174.10/issuetoc